PERAN CYBER PUBLIC RELATIONS HUMAS POLRI DALAM MEMBERIKAN PELAYANAN INFORMASI PUBLIK SECARA ONLINE - Yuliawati, Yuliawati; Pera Irawan, Enjang (Jurnal Politikom Indonesiana, 2016)
ABSTRACT This research entitled: The Role of Indonesian National Police at Public Relations division about Cyber Public Relations giving the public information services online. This research is motivated by the rise of the phenomenon of public services through cyber activity or online. As similar with other state institutions, the Indonesian National Police also has an obligation to provide public information services, as mandated in the Act Public Information. Uniquely humas.porli.go.id website is managed by the Police Public Relations Division, involving 380 operators and 32 operators at the police station at the police station. It definitely requires good coordination, and this is part of the task of Police Public Relations Division to synergize it. Therefore, researchers are interested in finding out more about how the role of cyber public relations implemented by Police Public Relations Division. Theories and concepts used in this research is the concept of public relations, cyber public relations, public services and public information. This research is a qualitative descriptive study. The results showed that the role of Police Public Relations Division in conducting cyber public relations activity is more dominant on the role as a tecnicion communication and facilitator communication. However the role of expert preciber communication and solving process facilitator remains, although not so dominant. The application of the concept of public relations is a form of cyber police commitment in providing the best service to the community, as well as support for the implementation of the Law on Public Information. The quality of services through the medium of Police Public Relations humas.polri.go.id website still needs to be improved, considering there are still things to be improved, such as improving the quality of human resources manager of the website, optimize the look of the website, complete the menus in the website, improve protections system. Keyword: Cyber Public Relations